The role of refugees in the underground economy of the European Union - Mihai Mutascu; Scott W. Hegerty (IZA Journal of Development and Migration, 2022)
This paper explores the impact of refugees on the size of the underground economy in 28 European Union countries over the period from 1998 to 2017. It applies a nonlinear methodology by employing dynamic panel threshold estimations. The main findings uncover a nonlinear connection between refugees and the informal economy with an inverted V-shape and a different magnitude of effects depending on the share of the refugee population. The underground economy is stimulated at a low level of refugee inflows (where immigrants make up <0.572% of the total population). Large inflows compress the underground economy, which increases competition in the labor market based on lower labor costs. Economic growth and international trade play a crucial role in reducing the size of the informal economy. Equally importantly, coherent unemployment policy and adequate regulation of illegal immigrants support this process.This paper explores the impact of refugees on the size of the underground economy in 28 European Union countries over the period from 1998 to 2017. It applies a nonlinear methodology by employing dynamic panel threshold estimations. The main findings uncover a nonlinear connection between refugees and the informal economy with an inverted V-shape and a different magnitude of effects depending on the share of the refugee population. The underground economy is stimulated at a low level of refugee inflows (where immigrants make up <0.572% of the total population). Large inflows compress the underground economy, which increases competition in the labor market based on lower labor costs. Economic growth and international trade play a crucial role in reducing the size of the informal economy. Equally importantly, coherent unemployment policy and adequate regulation of illegal immigrants support this process.
Keywords: F22; O17; C23; 330; refugees; underground economy; implications; European Union